No dar puntada sin hilo: bordados y guarniciones del siglo XVII = Seventeenth-century vocabulary related to embroidery and trimmings - Junquera Martínez, Alejandro (Estudios Humanísticos. Filología, 2020)
Dentro del estudio de la vestimenta, uno de los campos léxicos más interesantes es el del léxico relativo a los adornos y las guarniciones. Partiendo de los documentos notariales recopilados por el Corpus Léxico de Inventarios (CorLexIn), este estudio pretende ofrecer una descripción y análisis lexicográficos de diversos ítems léxicos concretos alusivos a elementos textiles de adorno que podrían englobarse bajo hiperónimos como flecos, bordados, cintas o pasamanerías. Within the study of clothing, one of the most interesting fields could be vocabulary referred to decorations and trimmings. Based on the notarial records gathered by the Corpus Léxico de Inventarios (CorLexIn), this study aims to offer a lexicographical description and analysis of some specific lexical items that refer to textile adornment elements that could be included under hyperonyms such as tassels, embroideries, ribbons or trimmings.